Analysis of Product Quality and Advertising on the Purchase Intention of Opak Oded Consumers in Sumedang - Henny Utarsih (International Journal of Marketing and Digital Creative, 2026)
The 'New Normal' period caused by the ongoing Covid-19 pandemic has had a profound impact on Opak Oded’s business, with income turnover reduced by 75%. This sharp decline is primarily attributed to disruptions in distribution channels, which have significantly affected business operations and led to a reduction in staff from 70 to 43 employees. This study aims to examine the influence of product quality and advertising on the purchasing intentions of Opak Oded customers in the Sumedang region. A quantitative descriptive analysis method was employed, using a survey of 96 participants. Data were analyzed using Structural Equation Modeling (SEM) with Smart PLS 3.0 software to assess the relationship between product quality, advertising, and purchase intention. The findings reveal that both product quality and advertising have a significant and positive effect on individuals' intentions to buy Opak Oded products. Moreover, these two factors combined have a substantial influence on purchase intention. The novelty of this research lies in its focus on a traditional local product during the pandemic, providing insights into how small businesses can adapt their marketing strategies during economic downturns. However, this study is limited to one geographic location (Sumedang) and the goods delivery sector.